Réponses

2014-09-07T11:35:42+02:00
(+3) - 5 - (- 3) - 6 + (- 2) + 8
= 3 - 5 + 3 - 6 - 2 + 8
= 3 + 3 + 8 -5 - 6 - 2
= 14 - 13
= 1

(- 3) + (- 10)  =  - 3 - 10 = - 13

(+ 6) - (+ 7) = 6 - 7 = - 1

-6 - 28  = - 34 

7 - 12 = -  5

- 12 + 5 = - 7

(- 11) - (- 3)  = - 11 + 3 = - 8

5/7 - 2/7 = 3/7

3/8 + 13/24
= 3 x 3 / 8 x 3 + 13/24
= 9/24 + 13/24
= 22/24
= 2 x 11 / 2 x 12
= 11/12

7/9 x 8/5 = 56/45

12/77 x 35/30
= 420/2310
= 210 x 2 / 210 x 11
= 2/11

2/3 - 1/3 x 7/4
= 2/3 - 7/12
= 2 x 4 / 3 x 4 - 7/12
= 8/12 - 7/12
= 1/12

(27/40 + 1/5) x (4/7 - 4/21)
=(27/40 + 1 x 8 / 5 x 8) x (4 x 3 / 7 x 3 - 4/21)
= (27/40 - 8/40) x (12/21 - 4/21)
= 19/40 x 8/21
= 152/840
= 8 x 19 / 8 x 105
= 19/105